The Usa-Iraqi Cultural Relations 1968-1979 - Mohammed Abdulla Kakasur; Harem Hasan Ahmed Baban (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
In the last few years the relations btewen usa and the middle eastern countries,particulary with iraq in the period of the cold war.is one of the crucial topic among schooalars after iraq 2003 librartion.in general the relationship between usa and iraq 1968-1979 was not stable.howevr it can be showred that at that time iraq counted as the soviet union alliance.it can be noied that, the cultural relations between usa-iraq in the period 1968-1979 was limited.althought those relations were benifitial,particulary for devebeloping iraqi clture.the usa press attitude,usa higher education inistituin and the usa excavation temas in iraq were the most fameous cultural relations between iraq and usa. It can be said that,both countreis attempted to make a realtions with each others.for instance,iraqs necessity on the usa techonology educational expeirnce,while,the usa indigenced had a cultural relations with iraq,due to the importance of iraq in political,geopolitical ,economical role.as well as,iraq was the owner of (sumerian,assyrian,babylon…)civilazations.therfore,those factors attracted the usa foundation to work in iraq,those usa teams continued working in iraq in diffrnet fields until the iraqi government expulsioned them.